Calibration and validation of the rabbit model of electrolytic‐mediated arterial thrombosis against the standard‐of‐care anticoagulant apixaban - Pancras C. Wong; Earl Crain (Wiley, 2022)
Abstract Apixaban is a factor Xa (FXa) inhibitor and standard‐of‐care anticoagulant with FXa Ki and plasma protein binding (free fraction) averages 0.08 nM and 0.13 in humans and 0.16 nM and 0.37 in rabbits, respectively. Apixaban at the approved dose of 5 mg BID achieved maximum and minimum plasma concentration of 373 nM (95% CI: 198 - 699 nM) and 224 nM (95% CI 89-501 nM), respectively, in patients with nonvalvular atrial fibrillation (AF). We calibrated the rabbit model of electrolytic‐mediated arterial thrombosis (ECAT) against apixaban and correlated the potencies derived from the rabbit ECAT to in vivo efficacious exposure levels in AF patients. Vehicle and apixaban at multiple doses were infused IV in ECAT rabbits and their effects on thrombus weight were measured. Apixaban exhibited dose‐related efficacy in preventing thrombosis in ECAT rabbits with EC20, EC50, EC60, EC70 and EC80 of 18, 101, 169, 296, and 585 nM, respectively. After correcting for the human‐to‐rabbit potency based on FXa Ki and plasma protein binding, we estimated a rabbit‐equally‐effective plasma concentration of 157 and 259 nM to the trough and peak plasma concentration in AF patients treated with 5 mg BID of apixaban. These rabbit‐equally‐effective plasma concentrations matched well with the rabbit ECAT EC60 and EC70. This study supports the potential of the rabbit ECAT to predict in vivo therapeutic drug exposure of FXa inhibitors. Achieving human‐equally‐effective plasma concentrations to the rabbit ECAT EC60 and EC70 may produce clinical efficacy in patient populations like AF.